Legal Protection of Netflix’s Digital Content Copyright Against Illegal Account Sharing Practices in Indonesia - Murtanti Fajarrani Devi; Suherman Suherman (Jurnal Daulat Hukum, 2025)
The expansion of digital streaming services has reshaped how Indonesian audiences obtain entertainment, with platforms operating through Over-The-Top (OTT) distribution such as Netflix becoming central to daily media use. Alongside the economic opportunities created for the digital creative sector, this shift has also produced legal complications, especially regarding the protection of works that are made available exclusively in digital formats. A recurring concern involves the circulation of Netflix accounts that are exchanged, sold, or jointly used in ways that exceed the scope of legitimate subscription rights. Such practices allow individuals to enjoy paid content without holding their own access authorization, thereby interfering with the economic rights legally reserved for Netflix as the copyright owner. Although a number of scholars explore copyright enforcement in online environments, discussions focused on the legal treatment of account-sharing within Indonesia remain scarce. To address this issue, the present study examines how the protection of Netflix’s digital content is framed under Indonesia’s Copyright Law (Law No. 28 of 2014) and identifies doctrinal uncertainties as well as sociological factors that complicate enforcement efforts. The research is conducted through a normative methodology supported by statutory and conceptual approaches, utilizing legislation, academic commentary, and other relevant legal materials. The analysis shows that unauthorized sharing of subscription accounts contradicts the rights to distribute and communicate a work to the public, as provided in Article 9 of the Copyright Law. However, because the law does not explicitly regulate the sharing of paid digital accounts and public understanding of digital copyright obligations remains limited, a regulatory gap persists. The study therefore argues that improving the protection of copyrighted digital works requires clearer legislative direction, cooperation among state institutions, and broader public education on digital copyright norms to ensure that creators’ economic interests are adequately safeguarded and that Indonesia’s creative economy can continue to grow in a sustainable manner.